(untitled) (Web of Teachers: Inderscience Research, 2025)
This article is dedicated to the methodology of teaching medical terms in the German language, addressing key aspects necessary for the effective assimilation of medical vocabulary by students. The work analyzes the basics of medical terminology, particularly the role of Latin and Greek roots, prefixes, and suffixes in the formation of medical words. It also discusses the use of visual materials, such as anatomical maps and images, to enhance the perception of terms. The article emphasizes the importance of applying terms in the context of real clinical situations and examples, which helps students not only memorize words but also understand their practical use. The conclusion highlights the significance of regular repetition and testing of the material, which contributes to the long-term retention of terms and improves the quality of learning.